A 3D model reflecting the dynamic generating process of pore networks for geological porous media. (December 2021) - Lyu, Qifeng; Wu, Heng; Li, Xin
Abstract: Pore-network models are useful for simulating physical processes in geological porous media. Here in this paper, the network theories are used to analyze X-ray computed tomography (CT) images of geological porous media. Results show the traditional mathematical degree which represents the coordination number of pore networks is insufficient to describe the preferential-attachment mechanism of pore networks. Thus a new parameter, physical degree, was proposed, which represents a physical quantity of both a specific pore and its attached throats to facilitate the description of pore networks. By analyzing X-ray CT images of different geological porous media, it was found the mathematical degree follows a Poisson law whereas the physical degree can be fitted by a power law. This indicates the pore network of geological porous media is randomly scale free. But the scale free is volume dependent. When the power law breaks down, the scale-free quantity, such as porosity, becomes scale variant. Based on these findings, a pore-network model was proposed, which reflects the dynamic generating process of the pore network. And the randomness featured in mathematical degrees and volume-dependent scale free featured in physical degrees are contained in this model.